Wireless and mobile localization and tracking - Liang, Jian Lin (2018)
As technology becomes more advance, more and more people are owning multiple mobile device. Due to the nature of mobility of mobile device, it must rely on wireless to be able to communicate with another device or connect to the internet. As such, there is a growing need to analyze the spectrum to find the optimal channel out of all the overcrowding bands. The purpose of this project aims to research on the use of open source wireless driver, namely ath9k which has a spectral scan functionality, to scan for wireless information in the environment. Scanned data could possibly be used to create an interference classifier. To fulfill the requirement of this project, we propose the use of netlink which integrates into our user space application to collect the spectral data and display it to the user in real time. With the implementation of netlink as the communication between our kernel module and multi-threaded user space application, spectral data from the ath9k is received promptly without the need to go through debugfs. Some suggestion for future work includes extending the scanning to HT40 channels and possibly to also support ath10k drivers.